MEROSIN-DEFICIENT CONGENITAL MUSCULAR DYSTROPHY (CMD1A): CLINICAL CASE OF CONGENITAL MUSCULAR DYSTROPHY INVOLVING CENTRAL NERVOUS SYSTEM - O. A. Klochkova; A. L. Kurenkov; A. M. Mamed'yarov (Union of pediatricians of Russia, 2014)
Congenital muscular dystrophies (CMDs) are an extremely heterogenous group of neuromuscular diseases. The article presents the general information on clinical and pathogenetic aspects of CMD diagnosis with emphasis on one of the most common forms of nervous system disturbances - merosin-deficient congenital muscular dystrophy (CMD1A). The authors describe clinical pattern of CMD1A, pathogenesis, epidemiological data, approaches to instrumental, morphological and molecular genetic diagnosis, as well as symptomatic treatment and prenatal diagnosis in detail. As long as there are few genetically confirmed clinical cases of CMD1A described in the publications written in Russian, the authors present their 3-year-long follow-up of a child with genetically confirmed diagnosis of CMD1A (mutations c.2049_2050delAG and c.6993-2A > C of gene LAMA2 [compound heterozygous state]). The article presents a detailed discussion of the described case, comparison with results of recent foreign and Russian observational studies of CMD1A in children. It also contains information on differential diagnosis of CMD1A in the structure of other congenital myodystrophies and optimization of molecular genetic diagnosis.